2019
DOI: 10.1111/gwao.12403
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned openings and restraints: The meaning‐making of women professionals breaking into the male‐dominated sector of forestry

Abstract: This article addresses how women forestry professionals articulate and interpret their experiences of being a woman and a professional in the male-dominated context of forestry. The findings suggest that the entrance of women into forestry has created openings as well as restraints within the dominant discourses of forestry organizations. Gendered constructions of skills and a workplace culture described as built on homosocial values cause women to feel questioned and disadvantaged. At the same time, women are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 58 publications
2
31
0
Order By: Relevance
“…Networks for women were initially formed as a response to exclusionary practices in Swedish forestry, and they should be understood as a strategy by which to resist the subordination of hegemonic femininity in forestry. The interviewees clearly articulated their experience of Swedish forestry as a male space in which (hegemonic) masculinity is normative, which is in line with the findings from other studies on forestry (e.g., Lidestav 2016, Brandth andHaugen 2005;Johansson et al 2019a;Johansson, Johansson, and Andersson et al 2018;Lidestav and Egan Sj€ olander 2007;Reed 2003). Many interviewees brought up examples of exclusion in both symbolic and material forest spaces, i.e., exclusion from the idea of the forest as a male space, as well as exclusion in forest courses and activities, representation in forest owner associations, and from the use of material items such as forest gear and protective clothing (because of the sizes and designs being based on the male body).…”
Section: Negotiating Femininities and Challenging Hegemonic Masculinisupporting
confidence: 85%
See 1 more Smart Citation
“…Networks for women were initially formed as a response to exclusionary practices in Swedish forestry, and they should be understood as a strategy by which to resist the subordination of hegemonic femininity in forestry. The interviewees clearly articulated their experience of Swedish forestry as a male space in which (hegemonic) masculinity is normative, which is in line with the findings from other studies on forestry (e.g., Lidestav 2016, Brandth andHaugen 2005;Johansson et al 2019a;Johansson, Johansson, and Andersson et al 2018;Lidestav and Egan Sj€ olander 2007;Reed 2003). Many interviewees brought up examples of exclusion in both symbolic and material forest spaces, i.e., exclusion from the idea of the forest as a male space, as well as exclusion in forest courses and activities, representation in forest owner associations, and from the use of material items such as forest gear and protective clothing (because of the sizes and designs being based on the male body).…”
Section: Negotiating Femininities and Challenging Hegemonic Masculinisupporting
confidence: 85%
“…In the Scandinavian context, forestry has been described as 'an arena where hegemonic rural masculinity is expressed' (Brandth and Haugen 2005, 148;Lidestav and Egan Sj€ olander 2007). It has been shown how Swedish women forestry professionals feel questioned and disadvantaged (Johansson et al 2019a), and the #metoo movement also reached the forest sector. The use of the hashtag #slutavverkat revealed how harassment and sexualised forms of male control have diminished women's power in the sector (Johansson, Johansson, and Andersson et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Over the past 40 years, the gendered pattern of paid work has been transformed. Not only has there been a significant rise of female participation in the labour force (McDowell, 2015), women are also breaking through into traditionally maledominated fields (Johansson et al, 2019) and are holding more professional positions (McDowell, 2006). Despite making significant headway, women remain starkly underrepresented in senior positions (Baumgartner & Schneider, 2010;Glass & Cook, 2016).…”
Section: Contextualising Young Women Undergraduate's Expectations Of Gendered Work Spacesmentioning
confidence: 99%
“…As Maddrell et al (2016) found, these informal networks can be vital in securing work opportunities and making their jobs more enjoyable. However, women are often neglected from these networks, particularly if they are in a male-dominated environment (Johansson et al, 2019). This is significant because belonging to social networks in the workplace is important as employees are more likely to view ideas from someone in their social group more favourably than those who are excluded from it (Heilman, 2001).…”
Section: Anticipating Exclusionmentioning
confidence: 99%
“…Ever since Kanter's theorizing about tokens, the need for women to take on masculine characteristics to compete successfully in male-dominated organizations has been described and discussed by researchers on gender and organizations (Miller 2004;Demaiter & Adams 2009;Powell et al 2009;Derks et al 2011;Kark et al 2012, Einarsdottir et al 2018Baublyte et al 2019). However, there is also research that nuances this image: societal gender dynamics as well as organizational dynamics change over the years, and expectations towards managers become more relaxed, allowing for greater variation including in gendered behaviors (Muhr 2011;Johansson et al 2019). The importance of a particular organizational context is seldom elaborated in these studies.…”
Section: Tokens Power and Possibilitiesmentioning
confidence: 99%